Engineering magnetic chirality in FeGe nanocylinders: Exploring topological states for spintronic applications - Saavedra, Eduardo (2024)
Iron germanide (FeGe) emerges as a promising magnetic alloy for spintronics and high-density data storage, owing to its distinctive magnetic properties and compatibility with existing fabrication techniques. This compatibility enables the synthesis of customized FeGe nanocylinders characterized by chirality, where their magnetization asymmetrically twists. Within specific size parameters, these nanocylinders can accommodate skyrmions-swirling magnetic structures with significant implications for information storage and processing technologies. This study investigates the response of FeGe nanocylinders to external magnetic fields, focusing on how their magnetic properties vary with dimensions (diameter and length). Specifically, we analyze the impact of length on the pseudo-static properties of short FeGe nanocylinders and examine the average topological charge and remanence states across different aspect ratios. Our investigation underscores the relationship between chirality and diverse magnetization states in four types of nanocylinders with varying aspect ratios. This comprehensive analysis elucidates the connection between nanocylinder magnetic states and the average topological charge - a critical factor in advancing ultra-low-energy data storage and logic devices.